Hadith #107 - Sahih Muslim - Sufyan (Sahih Muslim)
I pledged allegiance to the Messenger of Allah may peace and blessings be upon him) on sincerity and well-wishing for every Muslim.
Grade: Sahih

Hadith #2458 - Sahih Muslim - Sufyan (Sahih Muslim)
I said to ‘Abd al-Rahman b. Qasim: Have you heard from your father narrating from ‘A’isha (Allah be pleased with her) that he kissed her while observing fast? He (‘Abd al-Rahman b. Qasim) kept silence for a short while and then said:” Yes.”
Grade: Sahih

Hadith #2584 - Sahih Muslim - Sufyan (Sahih Muslim)
” Fasting of two months.”
Grade: Sahih

Hadith #2952 - Sahih Muslim - Sufyan (Sahih Muslim)
” That he (‘Umar) said: But I saw Abu’l-Qasim (way peace be upon him) having great love for you.” And he did not mention about clinging to it.
Grade: Sahih

Hadith #3242 - Sahih Muslim - Sufyan (Sahih Muslim)
Syria will be conquered and some people will go out of Medina along with their families driving their camels. and Medina is better for them if they were to know it. Then Yemen will be conquered and some people will go out of Medina along with their families driving their camels, and Medina is better for them if they were to know it. Then Iraq will be conquered and some people will go out of it along with their families driving their camels, and Medina is better for them if they were to know it.
Grade: Sahih

Hadith #3243 - Sahih Muslim - Sufyan (Sahih Muslim)
Yemen will be conquered and some people will go away (to that country) driving their camels and carrying their families on them and those who are under their authority, while Medina is better for them if they were to know it. Then Syria will be conquered and some people will go away driving their camels along with them and carrying their families with them and those who are under their authority, while Medina is better for theni if they were to know it. Thtn lraq will be conquered and some peopl
Grade: Sahih

Hadith #3355 - Sahih Muslim - Sufyan (Sahih Muslim)
A woman who has been previously married (Thayyib) has more right to her person than her guardian; and a virgin’s father must ask her consent from her, her consent being her silence, At times he said: Her silence is her affirmation.
Grade: Sahih

Hadith #3400 - Sahih Muslim - Sufyan (Sahih Muslim)
I said to Zuhri: Abu Bakr, what does this hadith mean:” The worst kind of food is at a wedding feast of the rich”? He laughed and said: The food served in the feast given by the rich is not worst (in itself). Sufyan said: My father was rich, so I felt disturbed when I heard this hadith, so I asked Zuhri who said: I heard from ‘Abd al-Rahman al-Alraj that he heard Abu Huraira (Allah he pleased with him) say: The worst kind of food is that served at the wedding feast. The rest of the hadith
Grade: Sahih

Hadith #3907 - Sahih Muslim - Sufyan (Sahih Muslim)
I heard Messenger of Allah (ﷺ) as saying: He who kept a dog (other than that) which is indispensable for watching the field or the animals would lose one qirat out of his deeds every day. As-Sa’ib b Yazid (one of the narrators) said: Did you hear it from Allah’s Messenger (ﷺ)? He said: Yes. by the Lord of this mosque.
Grade: Sahih

Hadith #7272 - Sahih Muslim - Sufyan (Sahih Muslim)
” We could not afford to eat to the fill even dates and water.”
Grade: Sahih

Hadith #7293 - Sahih Muslim - Sufyan (Sahih Muslim)
” I did not hear anyone saying besides him that it was Allah’s Messenger (ﷺ) who had said so.”
Grade: Sahih